Tomb of the sun king eaudiobook - Benson, Jacquelyn (Raiders of the Arcana, 2025)
Respectable lady scholars shouldn't be dodging evildoers, escaping lost tombs, and chasing down magical artifacts. Archivist and suffragette Ellie Mallory always dreamed of putting her scholarly skills to work in the ancient sands of Egypt. She never imagined she would be doing so in order to save an object of legendary power from a batch of ruthless villains. Racing baddies to an arcanum of Biblical proportions is only one of Ellie's problems. Her hopelessly academic and perpetually mortified step-brother, Dr. Neil Fairfax, is about to learn that she's been gallivanting around the globe with his danger-magnet best friend, Adam Bates—the roguish surveyor for whom Ellie harbors increasingly complicated feelings. Add the petite and terrifyingly fearless Constance Tyrrell to the mix, and Ellie either has a crack team of artifact-saving experts to hand... or a recipe for disaster. Together, they'll need to follow a trail of three-thousand-year-old clues from the necropolis of Saqqara to the temples of Luxor and beyond, where the ruined capital of a heretic pharaoh hides a secret with the potential to upend history. To keep an earth-shattering magic from falling into the wrong hands, Ellie will need to pull out all the stops—even if that means resorting to fisticuffs, ignoring proper archaeological processes... and solving one of Egypt's greatest mysteries. Dive into Tomb of the Sun King to experience the next action-packed historical fantasy adventure in the Raiders of the Arcana series, narrated by SOVAS award-nominated voice actor Alex Picard.